Training management of high jumpers based on phisical readiness control - Sirotkin, D. G. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The development of control methods of special physical readiness of athletes-jumpers dedicated to this research. In cooperation with model characteristics, the following control method allows to make a conclusion about the development of individual sides of the special preparation of sportsmen and as the result to carry out the corrections of the preparation process.